Becoming social media savvy: using Web 2.0 to enhance education - Yarrow, Linda (My University, 2012)
Health educators empower individuals with knowledge to improve health. In addition to traditional teaching methods, social media, such as Wikis, blogs, Twitter, Facebook, and YouTube, can be used. Information is available from social media outlets 24 hours a day, 7 days a week. Through social media, clients receive professional opinions as well as real-world information and emotional support from others dealing with similar health situations. Helping patients connect with others as a support system and educational resource should be part of the patient prescription for total care.
Keywords: Education; Online health; Social media; Web 2.0